Oxidative Stress Response of Aspergillus oryzae Induced by Hydrogen Peroxide and Menadione Sodium Bisulfite - Shao, Huanhuan (Microorganisms, 2019)
Oxidative stress response protects organisms from deleterious effects of reactive oxygen species (ROS), which can damage cellular components and cause disturbance of the cellular homeostasis. Although the defensive biochemical mechanisms have been extensively studied in yeast and other filamentous fungi, little information is available about Aspergillus oryzae. We investigated the effect of two oxidant agents (menadione sodium bisulfite, MSB, and hydrogen peroxide, H(2)O(2)) on cellular growth and antioxidant enzyme induction in A. oryzae. Results indicated severe inhibition of biomass and conidia production when high concentration of oxidants was used. Transcriptomic analysis showed an up-regulated expression of genes involved in oxidoreduction, such as catalase, glutathione peroxidase, and superoxide dismutase. In addition, it was observed that oxidative stress stimuli enhanced the expression of Yap1 and Skn7 transcription factors. Further, metabolomic analysis showed that glutathione content was increased in the oxidative treatments when compared with the control. Moreover, the content of unsaturated fatty acid decreased with oxidative treatment accompanying with the down-regulated expression of genes involved in linoleic acid biosynthesis. This study provided a global transcriptome characterization of oxidative stress response in A. oryzae, and can offer multiple target genes for oxidative tolerance improvement via genetic engineering.